Premorbid personality traits and their course in mild cognitive impairment: results from a prospective population-based study in Germany - Kuźma, Elżbieta; Hildesheim, Christine; Toro, Pablo; Schönknecht, Peter; Schröder, Johannes (Dementia and geriatric cognitive disorders, 2011)
Background: Personality traits contribute to cognitive functioning. We present a study comparing personality traits in normal ageing and mild cognitive impairment (MCI).Methods: We conducted a representative longitudinal study including 222 subjects from a cohort born between 1930 and 1932 (n = 500) examined at three examination waves (t1: 1993/1994; t2: 1997/1998; t3: 2005/2007). Personality traits were assessed with the NEO-Five-Factor Inventory questionnaire. Results: Healthy controls and patients with MCI showed a significant (p < 0.05) decrease concerning their levels of neuroticism and extraversion over time. MCI subjects scored significantly higher on neuroticism at baseline and lower on openness at all examinations compared to healthy controls. Subjects with higher baseline neuroticism showed a 2.24 times higher risk of developing MCI at the third follow-up (odds ratio = 2.24, 95% confidence interval = 1.12-4.45 - scores adjusted for education and sex). Conclusions: MCI subjects differ in their premorbid personality traits compared to healthy controls. According to our study, higher neuroticism should be considered a risk factor for the development of MCI.
Gesehen am 12.07.2022